Is there a role for publication consultants and how should their contribution be recognized? - Kendall, G.; Yee, A.; McCollum, B. (Springer, 2016)
When a scientific paper, dissertation or thesis is published the author(s) have a duty to report who has contributed to the work. This recognition can take several forms such as authorship, relevant acknowledgments and by citing previous work. There is a growing industry where publication consultants will work with authors, research groups or even institutions to help get their work published, or help submit their dissertation/thesis. This help can range from proof reading, data collection, analysis (including statistics), helping with the literature review and identifying suitable journals/conferences. In this opinion article we question whether these external services are required, given that institutions should provide this support and that experienced researchers should be qualified to carry out these activities. If these services are used, we argue that their use should at least be made transparent either by the consultant being an author on the paper, or by being acknowledged on the paper, dissertation or thesis. We also argue that publication consultants should provide an annual return that details the papers, dissertations and thesis that they have consulted on.